In-vitro and In-silico evaluation of the inhibitory effects of Persea americana leaf extract against calcium oxalate stones - Akyol, Emel; Danisman, Merve; Oner, Mualla (SPRINGER, 2025)
This study investigated the effects of Persea americana extract (PAE) as a potential inhibitor of calcium oxalate monohydrate growth using both in-vitro and in-silico methods with spontaneous crystallization to evaluate its effectiveness in preventing kidney stones. X-ray diffraction was used to characterize the morphology of calcium oxalate (CaOx) crystals, while scanning electron microscopy (SEM) was used to determine their particle size and crystal formation patterns. SwissADME (Absorption, Distribution, Metabolism, Excretion) computational analysis predicted the biological activity of the extract. The experimental results show that the inhibition of crystal growth increases with the amount of PAE in solution, and crystal growth was almost completely inhibited for 450 min at a concentration of 100 mL of PAE. The in vitro results also revealed that Persea americana leaf promoted the formation of calcium oxalate dihydrate (COD) crystals rather than monohydrate crystals. These findings on PAE's inhibitory effect on calcium oxalate crystallization suggest that natural additives could be valuable in treating kidney stone disease.
Keywords: Persea americana extract (PAE); Renal calculi; SwissADME; Inhibitor; Calcium oxalate crystallization; CRYSTAL-GROWTH; AQUEOUS EXTRACT; CRYSTALLIZATION; MAGNESIUM; MORPHOLOGY; CITRATE; LEAVES; MILL; Urology & Nephrology